Rzeczywiste czy wyobrażone? Uszkodzenia, ubytki, deformacje posągów antycznych inspiracją dla multimedialnych działań wybranych artystów współczesnych - Pawełczyk, Dominika (Collectanea Philologica, 2015)
In this article I would like to show the potential of the destroyed ancient sculptures and thereforeto explore a variety of new themes and issues that may be generated through re-using the motivesby the artists. I was especially interested in creators, who undertook a multimedial game with traditionalsculpture representations, using the potential of performance art, photography, digital imageprocessing and computer photomontage.Mary Duffy by her performative actions showed that the deformed body of the ancient sculptureforms also her everyday reality. The damaged statue of “Venus de Milo” has become a usefulinspiration for stories about disability and discrimination.Maciej Osika chose the path of fantasy and aesthetisation of the damages. Graphic processedassemblies allowed him to tell us about the perfection of the human body, while Davide Bedonidecided to show that the sculptures can describe the infinite myth of harmony, which defects will becomplemented by the portraits of contemporary icons of beauty.The technique of exploring the audience has been chosen by French artist Diane Ducruetby showing “Passengers” to the viewers. The artist used the facial photographs of her loved onesthrough which fragments of well known, damaged Louvre sculptures are barely noticeable. Ducruettalks about the elusiveness of life by those damaged portraits. Likewise all the artists mentionedabove she also blurs the boundaries between what is real and what is imaginary.